Extended pre‐release holding with raspberry ketone and methoprene as supplements: Field performance of Bactrocera tryoni males. (18th November 2021) - Biswas, Md Jamil Hossain; Rempoulakis, Polychronis; Benelli, Maurizio; Adnan, Saleh Mohammad; Allen, Andrew P.; Taylor, Phillip W.; Mainali, Bishwo
Abstract: In Sterile Insect Technique (SIT) programs, the released sterile insects must attain sexual maturity at an early adult age so that a large proportion survive to mature and contribute to reducing reproduction of pest populations. Previous field studies based on release of adult Queensland fruit fly, Bactrocera tryoni (Froggatt) ('Q‐fly'), at 2 days of age found a significant increase in the recapture of mature male Q‐flies when they were provided methoprene or raspberry ketone (RK) before release. SIT for Q‐flies has subsequently adopted release at 5 days of age; there is now a contextual need to re‐assess the merit of methoprene and RK supplements. We assessed field abundance and dispersal of mature sterile male Q‐flies that had been held for 5 days on pre‐release standard diets of sugar and yeast hydrolysate (3:1) (control) with and without methoprene or RK supplements. Overall, the proportion of control‐ and RK‐treated flies recaptured was higher than the proportion of methoprene‐treated flies recaptured. We found no evidence that either methoprene or RK supplements yielded improvements over the control diet alone concerning abundance and dispersal of the male Q‐flies. Laboratory studies indicate that while the doses of methoprene (control + methoprene at 0.05% or 0.5%) and RK (control + RK at 1.25% or 5%) used in field releases at 2 days of age did not affect male longevity when sustenance was provided, these doses resulted in reduced longevity when no sustenance was provided. Furthermore, all doses of methoprene and RK used in field releases at 5 days of age reduced male longevity regardless of sustenance. At 5 days of age, the flies are already in an advanced state of maturity when released and in this context, it appears that additional pre‐release treatments of methoprene and RK provide no further improvement and may even be detrimental when nutrition is scarce.